2019
DOI: 10.1016/j.jmapro.2019.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Development of metal matrix composites by direct energy deposition of ‘satellited’ powders

Abstract: Limited research has been undertaken investigating the material design freedoms that are granted through the use of additive manufacturing methods, especially the development of materials specifically formulated for additive processes. In this study, a new material combination was evaluated for use with directed energy deposition methods. Here, a Ti-6Al-4V powder is processed in combination with a much finer titanium diboride powder following a satelliting procedure. The resulting combination consists of large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Farayibi et al [ 99 ] developed a new MMC using Ti6Al4V + titanium diboride in the powder form via a satelliting method. The resulted mixture consisted of large Ti6Al4V particles, enclosed within finer needle-shaped TiB structures, presented an improved hardness.…”
Section: Metal Matrix Composites (Mmcs)mentioning
confidence: 99%
“…Farayibi et al [ 99 ] developed a new MMC using Ti6Al4V + titanium diboride in the powder form via a satelliting method. The resulted mixture consisted of large Ti6Al4V particles, enclosed within finer needle-shaped TiB structures, presented an improved hardness.…”
Section: Metal Matrix Composites (Mmcs)mentioning
confidence: 99%
“…Their study successfully illustrated that the meltpool created by a laser during the L-PBF process is turbulent, mixing the liquid multiple times over before solidification can take place 30 . In fact, multiple studies have recently revealed that L-PBF melt pool turbulence can sufficiently disperse satellite ceramic particles into a metal matrix 18,23,24 . Figure 3(a) illustrates how it is believed this turbulent melt pool successfully dispersed the coated oxides into the metallic matrix of the build volume.…”
Section: Production Of Dispersion Strengthened Mpeas Via Additive Manmentioning
confidence: 99%
“…Studies have also shown that powder shape and size distribution contribute significantly to the quality of AM builds 21 . Other methods of incorporating nanoparticles into additive powder lots through chemical reactions or depositions have been explored; though the added complexity and expense of these techniques may limit their commercial viability 15,17,[22][23][24][25][26] .…”
mentioning
confidence: 99%
“…The main limitation of PM techniques is related to the price of raw material powders, which are expensive [125]. However, it should be noticed that the AM techniques, such as laser powder bed fusion (LPBF) and directed energy deposition (DED) processes, that are layer-wise manufacturing processes, are rapidly growing in the fabrication of MMNCs [126,127,128,129].…”
Section: Fabrication Of Mmncs Reinforced By Graphenementioning
confidence: 99%